Climate Resilient Communities in the Caribbean - Farny, Steffen (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2022)
This research report presents a transdisciplinary student research project on the development of climate resilience of communities on the Caribbean Island Dominica. The research was conducted through a partnership between the Leuphana University Lüneburg and the Sustainable Marine Financing Programme (SMF) of the GIZ. For the GIZ, the research project aimed at improving the understanding of the socio-ecological resilience framework for tackling problems of Marine Managed Areas and Marine Protected Areas. Also, it enabled new thoughts on how the GIZ and other development agencies can more effectively assists island states to better cope with the challenges of climate change. The role of the students from the “Global Environmental and Sustainability Sciences” programme of Leuphana University included the design of four transdisciplinary research projects to research aspects of resilience of Caribbean communities. The developing island states in the Caribbean are extremely vulnerable to more frequent and intense natural hazards while relying on the ecosystem services that are also at risk from extreme weather events, in particular Hurricanes. Low economic stability leads to a dependency of the states on international assistance. To decrease the vulnerability to shocks, counteracting measures that encourage learning and adaptation can increase the resilience against extreme weather events and their consequences. Concepts that were considered during the design of the transdisciplinary research projects were the adaptation of systems, diversity and stakeholder participation and resilience-focused management systems. Also, the students critically assessed the concept of foreign aid and how it can be successful, mitigating the risk of introducing neo-colonial structures. Flood Management, Biodiversity, Small-Scale Agriculture and Foreign Aid on Dominica were the topics of the transdisciplinary projects. The research methods of a literature review, stakeholder mapping, interviews, scenario development and visioning were used in the projects. In four scenarios developed in the ‘Flood Management’ project, it became evident that a broad as well as coordinated stakeholder engagement and a variety of measures are required for community resilience. A key finding of the ‘Biodiversity’ project was the identity dimension of community resilience, underlining the importance of the relationship between individuals and nature. The interlinkage of social identity processes and a resilient disaster response was also stressed by the project ‘Foreign Aid’, which highlighted that financial support is similarly important to inclusivity and reflexivity in the process of resource distribution. To recover from extreme weather events, the social memory also plays an important role. The project on ‘Small-scale Agriculture’ concluded, that the memory-making of local communities is as vital to community resilience as formal plans and trainings. The research project was based on the research approach of transdisciplinarity because of its solution-orientation. It links different academic disciplines and concepts, and non-scientific stakeholders are included to find solutions for societal and related scientific problems. In the four projects, principles of transdisciplinary research were party applied, but some challenges arose due to the geographical distance, time constraints and a strong focus on the scientific part in some phases. Nonetheless, the findings of the projects provide valuable learning lessons to be applied in practice and that can prove useful for future research.
A Transdisciplinary Student Research Project on Dominica
Keywords: 577 Ökologie